The Development of Personal Hygiene 3D Augmented Reality - Ali, Azita; Segar, Shamini (Research and Innovation in Technical and Vocational Education and Training, 2023)
This study aims to develop 3D augmented reality on Personal Hygiene Care. The development of this 3D augmented reality will provide understanding and awareness to the community. This 3D augmented reality design and development process generally uses the Waterfall development model. The model consists of six phases, namely planning, analysis, design, development, implementation and testing, and maintenance. In this study, there are six (6) experts consisting of three (3) lecturers, namely two (2) lecturers from the field of Creative Multimedia from the Faculty of Technical and Vocational Education, UTHM, and one (1) lecturer who is an experienced Multimedia Expert and IoT from the Faculty of Electronic Engineering Technology UniMAP. Meanwhile, three (3) other officers and nurses with educational backgrounds under the Ministry of Health Malaysia from Kuala Lumpur Hospital. The data analyzed found that experts agreed with the content and interface of the development of 3D augmented reality on personal hygiene. The development of 3D augmented reality can attract the interest of users because of the realistic shape of 3D animation. The development of 3D augmented reality can also provide awareness of good Personal Hygiene to the community, schools, and hospitals. Finally, the development of 3D augmented reality will have a positive impact on presenting information more effectively and easily understood by users.